Cutting performance of advanced multilayer coated (TiAlN/AlCrN) in machining of AISI D2 hardened steel - Jasni, Nur Akmal Hakim (2013)
The hard machining of hardened steel with advanced cutting tool has several advantages over conventional method such as short cycle time, process flexibility, compatible surface roughness, higher material removal rate and less environment problems with absence of cutting fluid. However, caused severe tool wear and changes to quality and performance of product due to higher mechanical stress and heat generation. Thus, proper criteria should be adopted to keep the longer tool life and maintaining the quality of surface integrity. In this work, an experimental investigation was conducted to characterize the machinability of multilayer TiAlN/AlCrN coated carbide tools and surface integrity in end milling of AISI D2 hardened steel (58-62 HRC) on a Vertical Machining Centre (VMC). The cutting variables were cutting speed (80-120 m/min) and radial depth of cut (3-5 mm), meanwhile feed per tooth (0.05 mm) and depth of cut (0.5 mm) were kept constant. Tool life and volume of material removed decreased as cutting speed and radial depth of cut increased due to higher temperature and contact area. Built-up edge formation, groove formation, and edge chipping were the dominant tool failure modes; however, the cutting tool was subjected to adhesion and abrasive wear for the duration of testing. The highest volume of material removed and tool life were 1500 mm and 4.97 min which associate to cutting speed of 100 m/min and radial depth of cut of 4 mm. The surface roughness, Ra values attained throughout the experiments were in range of 0.20 to 0.45 μm which may acceptable in mould and die fabrication. The optical microscope observations show that the milled surface is anisotropic in nature. Meanwhile, the surface defects observed during machining included feed marks, grooves, microchips or debris and cavities and the existence of surface defects caused by thermal softening of the material and interaction between cutting tool and workpiece. This study showed that a thin layer of plastic deformation was formed in the immediate sub-surface of the workpiece, and the microhardness was altered to a depth of 0.28 mm beneath the machined surface due to high pressure and elevated heat. Nevertheless, all cutting tools experienced excessive coating delamination by crack and strip from the substrate due to high friction and thermal cycling generated and low toughness of the coating. It can be concluded that hard machining can be carried out for AISI D2 hardened steel with multilayer TiAlN/AlCrN coated carbide tooling because the process has been proven to produce high productivity and functional performance of quality machined parts with respect to surface integrity.